Legal and political challenges of European Union’s cyber-diplomacy in the age of surveillance capitalism - Gaspersons, Jānis (Riga Graduate School of Law, 2021)
Bachelor thesis will focus on one of the initiatives, which has been developed in order to address the challenges, which are posed by the technological and digital advancements – cyber diplomacy. Furthermore, in order to put cyber-diplomacy into perspective, and more successfully evaluate its strengths and weaknesses, author will put it in the context of surveillance capitalism, which can be considered as one of the largest threats to cyberspace. Divided into two predominant parts – theoretical and empirical – thesis attempts to evaluate the efficacy of European Union cyber diplomacy in the context of surveillance capitalism. Within the scope of the thesis, author distinguishes the challenges that surveillance capitalisms have posed from both political and legal dimensions and discusses the potential of European Union cyber diplomacy in mitigating the effect that surveillance capitalism has on the fundamental rights of European Union citizens.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Cyberdiplomacy